Community strategies to promote sustainable wetland-based food security in rural areas of Zimbabwe - Marambanyika, Thomas; Beckedahl, Heinz; Ngetar, Njoya S. (Springer Verlag, 2016)
This article explores the various strategies rural households employ to sustain wetland use and conservation in the context of the restrictions imposed by the existing legal framework in Zimbabwe. Wetland cultivation is a common feature of the rural landscape and is mainly triggered by subsistence households endeavouring to stabilize their food security, especially in semi-arid and arid environments of the developing countries. Data was collected through a household questionnaire survey, key informant interviews, document review and direct observations. Quantitative data was analysed using ANOVA, Spearman Correlation Coefficient and Wilcoxon in Statistical Package for Social Scientists, whereas qualitative data was subjected to thematic analysis. The results revealed that most households adjacent to wetlands were food secure as wetland conditions enable the provision of a wide range of crops and natural products, contributing almost half of the food directly consumed and 48.2 % of average annual household total cash income. It was also observed that various soil and water conservation practices were adopted and local institutional arrangements were put in place to oversee their effective implementation. Thus, the general result has been increased wetland productivity, improved livelihoods and ecosystem protection. This has largely rendered the impact of legislation restricting wetland cultivation subtle in the local context. The study concluded that there is a need to promote participatory wetland management based on low-cost approaches sensitive to local conditions and the needs and practices of the local communities.